Disaster Communication among Flash Flood Victims in Garut Regency - Milyane, Tita Melia; Djuwita, Amalia; Parsono, Slamet; Mukhlisiana , Lusy (Mediator: Jurnal Komunikasi, 2024)
This study focuses on disaster communication among victims of flash floods on Friday night, July 15, 2022. According to data from the Regional Disaster Management Agency (BPBD), the severe rain caused 112 places to flood, 27 areas to experience landslides, and nine regions to experience floods and landslides simultaneously. This study aims to determine how the local government handles disaster communication and how victims of flash floods react to government-managed disaster relief efforts.  The theories used are public communication theory and the concept of disaster communication. The methodology used is qualitative, with data collection techniques through in-depth interviews with victims and local governments and literature reviews. The results showed that the government has tried to deal with the impact of flooding and communicate it through radio media, local newspapers, civil apparatus, and community empowerment and family welfare (PKK); however, after the flood was over, some residents chose to stay at the location for various reasons and considerations. In contrast, some other residents decided to occupy a new residence provided by the local government. The government also uses social media and WhatsApp groups to coordinate with related agencies and community elements.